Construction and validation of an Entrepreneurship Measurement Instrument for nursing students - del Arco Bravo, Isabel; Muñoz Gimeno, Mercé (Investigación y Educación en Enfermería, 2024)
Objective. To develop a valid and reliable scale to measure entrepreneurship competences of nursing students, by assessing the level of development of diverse entrepreneurship dimensions. Methods. An Entrepreneurship Measurement Instrument, Catalonia (IME.Cat) was constructed, by adapting two existing instruments, and a psychometric study was performed to address the validity of the content and the construct, and the reliability. The internal consistency and the discrimination capacity of the instrument’s items were examined. Results. The IME.Cat scale showed a high reliability (α=0.89) for the complete set of items. The Cronbach’s α value of the individual dimensions were: Problem management=0.78; Creativity=0.76; Personal confidence =0.64; and Risk acceptance =0.46. The corrected homogeneity indices for each of the item in the instrument were high (>0.40). The Confirmatory Factorial Analysis validated the proposed structure of the items according to dimension. Conclusion. The IME.Cat scale showed solid psychometric values for assessing the entrepreneurship competences of nursing students within its dimensions, which are fundamental for the professional development of nursing.